Implementation of environmental monitoring based on KAA IoT platform - M. Udin Harun Al Rasyid; M. Husni Mubarrok; Jauari Akhmad Nur Hasim (Institute of Advanced Engineering and Science, 2020)
Wireless sensor network (WSN) is a key to access the internet of things (IoT). The popularity of IoT and the prediction that there will be more devices connected to the Internet cause difficulties in integrating and making connected devices. The problem of IoT implementation are the lack of real-time data collection, processing, and the inability to provide continuous monitoring. To overcome these problems, this paper proposes an IoT device for monitoring environmental conditions through the IoT KAA platform that can be monitored anywhere and anytime in real time. The end device node consists of several sensors such as as temperature, humidity, carbon monoxide (CO) and carbon dioxide (CO2) sensors. The collected data from the end device node will be transmitted via a communication based on IEEE 802.15.4 to Raspberry Pi gateway, then sent to the KAA cloud server and saved into the database. The environmental data can be accessed via a web-based sensor application. We Analize the performance evaluation in terms of transaction, availability, data transfer, response time, transaction rate, throughput, and concurrency. The experimental result shows that the use of KAA IoT platform is better than that without platform.